Komparasi Kinerja Keuangan Sebelum Dan Sesudah Merger Dan Akuisisi Pada Perusahaan Pengakuisisi Di BEI - Neneng Sri Suprihatin (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2022)
This study aims to empirically examine the differences in financial performance between before and after mergers and acquisitions using several financial ratio variables including Current Ratio (CR), Debt to Asset Ratio (DAR), Total Asset Turnover (TATO), Net Profit Margin ( NPM), Return on Assets (ROA), Return on Equity (ROE), Earning Per Share (EPS), Price Earning Ratio (PER). This research is a quantitative research using a comparative research design. The research data is sourced from the IDX which takes data from companies that carried out mergers and acquisitions in 2015 and four years after conducting mergers and acquisitions in 2015 so that the period of this research is in 2013-2019. The sample selection was taken by purposive sampling method from a total of 34 companies obtained 10 companies that meet the criteria taken as a sample with an observation period of 7 years then obtained a total of 70 data sampling data. The research method uses a different test with the results of the study, among others, that there are differences in financial performance between before and after the merger with several variations of the year using the variables Current Ratio (CR), Debt to Asset Ratio (DAR), Total Asset Turnover (TATO), Return on Assets. (ROA), Return on Equity (ROE) but there is also no difference in financial performance between before and after the merger using the variable net profit margin (NPM), Earning per share (EPS), and Price Earning Ratio (PER).